The impact of consumer inattention on insurer pricing in the Medicare Part D program. (13th November 2017) - Ho, Kate; Hogan, Joseph; Scott Morton, Fiona
Abstract: The Medicare Part D program relies on consumer choice to provide insurers with incentives to offer low‐priced, high‐quality pharmaceutical insurance plans. We demonstrate that consumers switch plans infrequently and search imperfectly. We estimate a model of consumer plan choice with inattentive consumers and show that high observed premiums are consistent with insurers profiting from consumer inertia. We estimate the reduction in steady state plan premiums if all consumers were attentive. An average consumer could save $1050 over three years; government savings in the same period could amount to $1.3 billion or 1% of the cost of subsidizing the relevant enrollees.